2012
DOI: 10.1111/pbi.12018
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing analysis of the transcriptomes of peanut aerial and subterranean young pods identifies candidate genes related to early embryo abortion

Abstract: SummaryThe failure of peg penetration into the soil leads to seed abortion in peanut. Knowledge of genes involved in these processes is comparatively deficient. Here, we used RNA-seq to gain insights into transcriptomes of aerial and subterranean pods. More than 2 million transcript reads with an average length of 396 bp were generated from one aerial (AP) and two subterranean (SP1 and SP2) pod libraries using pyrosequencing technology. After assembly, sets of 49 632, 49 952 and 50 494 from a total of 74 974 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
83
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 49 publications
5
83
0
Order By: Relevance
“…As shown in the previous study, the seed in aerial pods aborted at the 6 days after marked (DAM) (Chen et al 2013). To identify differentially expressed genes (DEGs) relating to seed abortion during peanut aerial and subterranean pods development, we used a customized NimblerGen onligonucleotide microarrays at the 1, 2, 4, 8 DAM.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…As shown in the previous study, the seed in aerial pods aborted at the 6 days after marked (DAM) (Chen et al 2013). To identify differentially expressed genes (DEGs) relating to seed abortion during peanut aerial and subterranean pods development, we used a customized NimblerGen onligonucleotide microarrays at the 1, 2, 4, 8 DAM.…”
Section: Resultsmentioning
confidence: 62%
“…However, only until the peg carries the ovule into the soil where can the pod normally swell to allow room for the embryo to grow and eventually become subterranean pod (Feng et al 1995; Moctezuma and Feldman 1999, 2003). The failure of peg penetration into the soil leads to suppression of pod swelling initiation and form aerial pod, finally causing seed abortion and seriously impacting on the peanut production (Chen et al 2013). For instance, when gynophore penetration into the soil is prevented by any means of a physical barrier but still under a light treatment, the pod will not form normally (Zamski and Ziv 1976; Thompson et al 1985; Moctezuma 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have focused on furthering our understanding of the gynophore development. Chen et al (2013) took advantage of available transcriptome data to detect two cell-aging transcripts that significantly increased in the late stage of unburied gynophores and may participate in the abortion of gynophores on the ground. Xia et al (2013) found that a series of transcripts, including endogenous hormones, respond to optical signals, and that morphogenesis and cell division pathway transcripts showed distinct changes before and after the burying of the gynophore.…”
Section: Introductionmentioning
confidence: 99%